(3eSGdc GdNdGU aj egGdc GdNhGUs - (3WGTcHQj RGOI , YUGe GdOjf CHh GdNjQ CMeO Hf eUWaj Hf Ndjd, WGTcHQj RGOg,J (B968 (3g` s
(3ChdgG (B:s
(3hHYO aOhfc CjgG Gdedbi CeG GdChd agh GdMHQ s
(3BNQgG (B:s
(3hddEfUGa QGYjkG abO fdJ efgG s
(3hgh ai GdeMGceI Hjf GdJaJGRGfi hGdTQja GdLQLGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B257s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B(5669) s
Keywords: (3GdHdGZIs